Cohort profile: the Flu Watch Study - Fragaszy, Ellen B.; Warren-Gash, Charlotte; Wang, Lili; Copas, Andrew; Dukes, Oliver; Edmunds, W. John; Goonetilleke, Nile; Harvey, Gabrielle; Johnson, Anne M.; Kovar, Jana; Lim, Megan S.C.; McMichael, Andrew; et al. (Oxford University Press, 2016)
Influenza is a common, highly contagious respiratory virus which infects all age groups, causing a range of outcomes from asymptomatic infection and mild respiratory disease to severe respiratory disease and death.1 If infected, the adaptive immune system produces a humoral (antibody) and cell-mediated (T cell) immune response to fight the infection.2 Influenza viruses continually evolve through antigenic drift, resulting in slightly different ‘seasonal’ influenza strains circulating each year. Population-level antibody immunity to these seasonal viruses builds up over time, so in any given season only a proportion of the population is susceptible to the circulating strains. Occasionally, influenza A viruses evolve rapidly through antigenic shift by swapping genes with influenza viruses usually circulating in animals. This process creates an immunologically distinct virus to which the population may have little to no antibody immunity. The virus can result in a pandemic if a large portion of the population is susceptible and the virus is easily spread.